2016
DOI: 10.1111/jcmm.13015
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid inhibits EGFR/STAT1/3 and enhances p38/STAT1 signalling axis in breast cancer cells

Abstract: Tannic acid (TA), a naturally occurring polyphenol, is a potent anti‐oxidant with anti‐proliferative effects on multiple cancers. However, its ability to modulate gene‐specific expression of tumour suppressor genes and oncogenes has not been assessed. This work investigates the mechanism of TA to regulate canonical and non‐canonical STAT pathways to impose the gene‐specific induction of G1‐arrest and apoptosis. Regardless of the p53 status and membrane receptors, TA induced G1‐arrest and apoptosis in breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 57 publications
1
50
0
1
Order By: Relevance
“…Aside from the different time pattern, cell cycle modulatory effect of polyphenols might be another mechanism for their different mode of action. Studies suggested that EGCG and TA on cell cycle distribution are dependent on concentration, cell cycle states, and possibly cell types . EGCG has been reported to induce G1 arrest in MCF‐7 cells through modulating the expression of cell cycle regulators including Cdk2 and Cdk4 as well as mediating the induction of Cdk inhibitor p21 and p27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the different time pattern, cell cycle modulatory effect of polyphenols might be another mechanism for their different mode of action. Studies suggested that EGCG and TA on cell cycle distribution are dependent on concentration, cell cycle states, and possibly cell types . EGCG has been reported to induce G1 arrest in MCF‐7 cells through modulating the expression of cell cycle regulators including Cdk2 and Cdk4 as well as mediating the induction of Cdk inhibitor p21 and p27 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that EGCG and TA on cell cycle distribution are dependent on concentration, cell cycle states, and possibly cell types. [19][20][21] EGCG has been reported to induce G1 arrest in MCF-7 cells through modulating the expression of cell cycle regulators including Cdk2 and Cdk4 as well as mediating the induction of Cdk inhibitor p21 and p27. 22 In contrast, TA induced G1 arrest and mitochondrial apoptosis in YD-38 gingival cancer cells by inhibiting the Jak2/STAT3 signaling pathway.…”
Section: Combination Of Ta and Doxmentioning
confidence: 94%
“…Booth et al [32] performed a series of experiments in which ER-positive breast cancer cells, MCF7, and triple negative (ER − , PR − , HER2 − ) MDA-MB-231 along with nontumorigenic MCF10A were exposed to TA-cross-linked collagen type I beads. Growing cells remodeled collagen and released TA into surrounding medium leading to caspasemediated apoptosis.…”
Section: Breast Cancer Cellsmentioning
confidence: 99%
“…It was found that TA modulates the EGFR/Jak2/STAT3 pathway, inducing mitochondrial apoptosis in breast cancer cells lines: MCF-7, T47D, SK-BR 3, and MDA-MB-231. Moreover, both the enhancement of STAT1 ser727 phosphorylation and the inhibition of STAT1 tyr701 phosphorylation were discovered as the key factors leading to G1 arrest upon TA treatment [32].…”
Section: Breast Cancer Cellsmentioning
confidence: 99%
“…Tannic acid (TA) is a naturally occurring polyphenol found in red wine, grapes, beans, tea, coffee, nuts and various vegetables and fruits. Several studies have shown that TA has a potential activity in cancer prevention [ 199 , 200 , 201 , 202 , 203 , 204 ]. Cosan et al [ 168 ] have investigated the impacts of TA on telomerase activity, cell viability, number of cells and DNA fragmentation in human breast (MCF-7) and human colon cancer (CaCo-2) cell lines.…”
Section: Telomerase Inhibitors From Natural Productsmentioning
confidence: 99%